STUDENT ATTITUDE TOWARD THE USE OF WHATSAPP IN EFL CLASS - Emeliya Sukma Dara Damanik (UIN Sumatera Utara, 2019)
This paper is grounded by the utilizing of WhatsApp as media in teaching learning process. There are a lot of education practitioners who has conducted the use of WhatsAppin classroom. Therefore, the writer interested to investigate how students attitude inutilizing WhatsApp as the media in their learning. The writer converts the questioner into descriptive research . After analyzing of the data, the researcher found that the student has a positive impact toward the use of WhatsApp in classroom. Deal to this result, the researcher suggests that the reader can utilizeWhatsApp effectively to reduce the weakness of whatApp and combine to others method or strategy to reach the goal.